Infrasound observation at JapaneseAntarctic Station "Syowa": 11 years observations and results ... - Ishihara, Yoshiaki; Murayama, Takahiko; Yamamoto, Masa-yuki; Matsushima, Takeshi; Kanao, Masaki (Arctic Data archive System (ADS), Japan, 2020)
Infrasound observation at Syowa Station (SYO), Antarcticastarted as one of the projects related International Polar Year (IPY2007 - 2008) as one-sensor pilot observation, and after the pilot observation, we then migrateto 3-sensor arrayed observation. The obtained 11 years infrasound data enable us to examine characteristics of infrasound behavior around SYO. Spectralanalysis of recorded data clearly shows continuous arrivals of microbaroms fromsouthern ocean and weak annual change of the energy. Array analysis of the 3-sensor observation data detected infrasound signals generated by ice-relatedactivities around SYO. ...